MANAJEMEN PENDIDIKAN LITERASI DALAM PERSPEKTIF GERAKAN LITERASI SEKOLAH - Siti Rahmah; Salis Masruhi; Kholil Lur Rochman (Jurnal Manajemen Pendidikan, 2026)
The low quality of students evident in various national evaluations highlights the importance of strengthening literacy education management in schools. Although the School Literacy Movement (GLS) has been implemented at various levels, various studies show that its implementation has not been consistent, especially in terms of planning, organization, utilization of facilities, and monitoring. Based on these conditions, this study aims to critically analyze how literacy education management is practiced within the framework of GLS, while identifying the main challenges that hinder its effectiveness. This study uses a qualitative approach with a literature study method; data was obtained from journal articles, GLS evaluation reports, and relevant official publications from the Ministry of Education and Culture. The results show that the effectiveness of GLS is still hampered by four main problems: disparities between schools in managerial capacity, low teacher competence, inequality in literacy facilities, and weak evaluation that has not become part of school culture. These findings confirm that GLS is not yet an integral part of school management but still runs as an additional program.